Effects of Young Corn Ear Addition on Nutritional Composition and Acceptability of Malaysian Star Cake (Baulu Cermai)(Kesan Penambahan Jagung Muda Terhadap Komposisi Pemakanan dan Penerimaan Kek Bintang Malaysia (Baulu Cermai)) - Wan Rosli, W. I.; Chow, Yuh Nien (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2014)
Sufficient intakes of functional foods containing significant amount of dietary fibre in daily diet are beneficial to human health especially in preventing the prevalence of non-communicable diseases (NCDs). In this study, young corn powder (YCP) was added into Malaysian star cake (Baulu Cermai) to replace wheat flour (WF) partially at the formulations of 5, 10 and 15%. Baulu Cermai with 100% WF and 0% YCP was used as the control. The aim of the present study was to evaluate the effects of YCP addition on the nutritional composition, textural properties and sensory attributes of Baulu Cermai. The results showed that the mean values of moisture, ash, fat and protein content of Baulu Cermai increased in line with the levels of YCP incorporation. In addition, the total dietary fibre (TDF) content was increased proportionally with the increasing levels of YCP added into Baulu Cermai. Addition of YCP did not show any predictable trend in all the textural properties of Baulu Cermai. Meanwhile, the aroma, chewiness and tenderness increased in parallel with the increasing percentages of YCP added in the formulated products. Baulu Cermai added with 10% of YCP showed the highest score of overall acceptance. Addition of YCP at 10% into Baulu Cermai increases moisture, ash, fat, protein and total dietary fibre content without significantly affecting the textural properties and the sensory attributes of Baulu Cermai. Addition of YCP at 5% to replace WF partially in Baulu Cermai resulted in slight improvement of TDF and fat but does not affected moisture, ash, protein content and acceptability of the consumers. || Pengambilan makanan berfungsi yang mengandungi serat dietari yang signifikan dalam diet harian memberi manfaat kepada kesihatan manusia terutama sekali dalam membendung prevalens penyakit tidak berjangkit (NCD). Dalam kajian ini, tepung jagung muda (YCP) telah ditambahkan ke dalam kek bintang Malaysia (Baulu Cermai) menggantikan sebahagian tepung gandum (WF) pada tahap 5, 10 dan 15%. Baulu Cermai yang mengandungi 100% WF dan 0% YCP digunakan sebagai kawalan. Tujuan kajian ini adalah untuk menilai kesan penambahan YCP terhadap komposisi nutrien, ciri tesktur dan atribut sensori Baulu Cermai. Hasil kajian menunjukkan kandungan kelembapan, abu, lemak, protein dan serat Baulu Cermai bertambah seiringan dengan pertambahan peratus YCP. Sebagai tambahan, kandungan jumlah serat dietari (TDF) telah meningkat secara signifikan selari dengan peningkatan paras YCP dalam formulasi Baulu Cermai. Penambahan YCP dalam Baulu Cermai tidak menunjukkan sebarang corak dalam kesemua ciri tesktur. Di samping itu, atribut bau, kekunyahan dan kelembutan bertambah selari dengan peningkatan peratusan YCP dalam formulasi produk. Baulu Cermai yang mengandungi 10% YCP merupakan sampel yang paling disukai oleh para panel sensori. Penambahan YCP sebanyak 10% dalam Baulu Cermai meningkatkan kandungan lembapan, abu, lemak, protein dan TDF serta tidak mempengaruhi ciri tekstur dan atribut sensori Baulu Cermai. Penambahan YCP menggantikan sebahagian WF pada paras 5% meningkatkan sedikit kandungan TDF dan lemak tetapi tidak mempengaruhi kelembapan, abu, protein dan penerimaan pengguna.